2020
DOI: 10.1002/bmc.4762
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and anti‐complement activity of Glechomae Herba collected in different months

Abstract: Glechomae Herba (GH) is derived from the dried aerial part of Glechoma longituba (Nakai) Kupr., which is harvested from spring to autumn. It has the effects of clearing heat and detoxification. The aim of this paper was to study the chemical composition and the anti‐complement activity of GH collected in different months. Ultra‐high‐performance liquid chromatography coupled to quadrupole time‐of‐flight tandem mass spectrometry based on predicted compounds screening and diagnostic ion filter strategy was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Two ferulic acid derivatives were identified in kiwifruit samples, including ferulic acid 4-O-glucoside and ferulic acid 4-O-glucuronide. Ferulic acid 4-O-glucuronide was previously reported to be found in glechomae herba by Luo, et al [59].…”
Section: Hydroxycinnamic Acidsmentioning
confidence: 83%
“…Two ferulic acid derivatives were identified in kiwifruit samples, including ferulic acid 4-O-glucoside and ferulic acid 4-O-glucuronide. Ferulic acid 4-O-glucuronide was previously reported to be found in glechomae herba by Luo, et al [59].…”
Section: Hydroxycinnamic Acidsmentioning
confidence: 83%
“…Our previous published papers (Li et al, 2019; Luo et al, 2019, 2020) have summarized in detail the identification of chlorogenic acids and flavonoids in TCM. According to the reported DPIs and NL of chlorogenic acids and flavonoids (Supporting Information Figures S6 and S7), 9 chlorogenic acids and 24 flavonoids were identified in Yinqiao powder water decoction.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous published papers (Li et al, 2019;Luo et al, 2019Luo et al, , 2020 have summarized in detail the identification of chlorogenic acids and of this method was that the structures of new compounds could not be accurately identified. In the future, new compounds would be separated, and nuclear magnetic resonance would be applied to ensure their structures.…”
Section: Characterization Of Chlorogenic Acids and Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Luo et al used ultra-high-performance liquid chromatography coupled to quadrupole time-of-flight tandem mass analysis (UHPLC-QTOF-MS/MS) to identify 40 chlorogenic acids. 22 In the same year, Li et al also used this method to identify the chemical constituents such as caffeoylquinic acid, feruloylquinic acid, p -coumaroylquinic acid and di-caffeoylquinic acid in GH. 23 It was concluded that chlorogenic acids had anti-complement activity.…”
Section: Phytochemistrymentioning
confidence: 99%